Creation of a Suicide Mortality Review Board in Maine: In-Depth Evaluations Can Lead to Preventive Measures - Sarah Sherman (Maine Policy Review)
Given that Maine has the highest veteran suicide rate in the Northeast, the Maine Bureau of Veteran Services has been working to educate healthcare providers and the public about services available specifically for veterans. This commentary describes MBVS activities around this topic and the actions of Maine's Suicide Mortality Review Committee as they investigate the possibility of establishing a Suicide Mortality Review Board.